From Moses to Maggie: Popular Political Wisdom and the Republican Tradition in Political Thought - de Haan, Ido (Javnost-The Public, 2000)
Popular political wisdom is often represented as a form of anti-politics, or Politikverdrossenheit, and therefore as detrimental to the health of the democratic political body. Recently, this negative interpretation of popular political wisdom has been revived in reaction to the growth of rightwing parties in Europe, who seem to be able to mobilise an uncanny, prejudiced and even racist public opinion. In this article, this negative interpretation is criticised as too onesided. It overlooks the democratic implications of populism and the populist, redemptive aspects of democratic politics. In a mythical sense, the populist tradition starts with the originary redemptive politician Moses, and goes on until the present time. Its historical roots can be retraced to a republican conception of politics. The tradition of civic self-government, the concomitant notion of the dangers of political corruption, and the way to overcome this predicament as it was developed in the citystates of the Italian Renaissance, form the conceptual and practical framework in which the politics of populism could have developed at the end of the nineteenth century. Moreover, this framework structures up until today the strategy and rhetoric of politicians who try to pursue the anti-political politics of populism.